Pengaruh Profitabilitas dan Kebijakan Utang terhadap Nilai Perusahaan: Studi Pada Perusahaan BUMN yang Terdaftar di BEI - Ambarwati, Jenny; Muslihat, Asep (The Double Entry Journal, 2022)
This study aims to examine the effect profitability and debt policy on firm value. This study was conducted on state – owned enterprises or Badan Usaha Milik Negara listed on the Indonesia Stock Exchange conducted in 2016 – 2020. The data collection method uses purposive sampling, and data analysis techniques used a multiple liniear regression. The results indicate that profitability as proxied by return on asset (ROA) had a positive effect on firm value. While the debt policy as proxied by debt to equity ratio (DER) does not affect the firm value.